Pemikiran sasterawan negara Shahnon Ahmad - Muhammad Haji Salleh 1942- (Siri kajian pemikiran sasterawan negara, 2012)
Literary criticism on the works of Shahnon Ahmad, a Malaysian writer; papers of a seminar